Pengaruh Cash Turnover, Total Asset Turnover, Receivable Turnover dan Sales Growth Terhadap Profitabilitas Pada Perusahaan Sub Sektor Kimia Yang Terdaftar di BEI Tahun 2020-2024 - Febrianto, Wira; Yunira, Haervi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the effect of Cash Turnover, Total Asset Turnover, Receivable Turnover, and Sales Growth on the profitability of chemical sub-sector companies listed on the Indonesia Stock Exchange during the period 2020 to 2024. Profitability is measured using Return on Assets. This study uses secondary data from annual financial reports with a purposive sampling technique. The sample consists of 7 companies with 35 data observations. Data analysis was performed through multiple linear regression using SPSS version 25.0. The results of the partial test indicate that Cash Turnover has a negative and significant effect on profitability, meaning that high cash turnover is actually associated with decreased profits. Total Asset Turnover has a positive and significant effect, indicating that efficient use of assets can improve financial performance. Receivable Turnover also has a positive and significant effect, indicating that companies that quickly collect receivables tend to have better profitability. However, Sales Growth does not have a significant effect on profitability, indicating that sales growth does not always increase net profit. Simultaneously, the four variables do not have a significant effect on profitability because the significance value is greater than 0.05. The Adjusted R² value of 0.247 indicates that 24.7 percent of the variation in profitability is explained by these variables, with the remainder influenced by other factors. This study implies that management needs to focus on cash, asset, and receivable efficiency to improve profitability.